Cytocompatibility and response of osteoblastic-like cells to starch-based polymers : effect of several additives and processing conditions - Gomes, Manuela E. (2001)
This work reports on the biocompatibility evaluation of new biodegradable starch-based polymers that are under consideration for use in orthopaedic temporary applications and as tissue engineering scaffolds. It has been shown in previous works that by using these polymers it is both possible to produce polymer/hydroxyapatite (HA) composites (with or without the use of coupling agents) with mechanical properties matching those of the human bone, and to obtain 3D structures generated by solid blowing agents, that are suitable for tissue engineering applications. This study was focused on establishing the influence of several additives (ceramic fillers, blowing agents and coupling agents) and processing methods/conditions on the biocompatibility of the materials described above. The cytotoxicity of the materials was evaluated using cell culture methods, according to ISO/EN 109935 guidelines. A cell suspension of human osteosarcoma cells (HOS) was also seeded on a blend of corn starch with ethylene vinyl alcohol (SEVA-C) and on SEVA-C/HA composites, in order to have a preliminary indication on cell adhesion and proliferation on the materials surface. In general, the obtained results show that all the different materials based on SEVA-C, (which are being investigated for use in several biomedical applications), as well as all the additives (including the novel coupling agents) and different processing methods required to obtain the different properties/products, can be used without inducing a cytotoxic behaviour to the developed biomaterials